Persepsi penggunaan ICT dalam pengajaran Pendidikan Jasmani dan Pendidikan Kesihatan - Thanabalan, Muniandy (2008)
This research is carried out in order to find out the level of ICT skills and perception towards the utilization of ICT in teaching and learning the Physical Education among PE teachers in Sarawak. Respondent for this study involved 340 PE teachers from secondary schools in Sarawak. Questionnaire is used as a research insrument. This summary of findings showed that ICT skills among most of the PE teachers are at the moderate level. Regarding perception of PE teachers towards utilization of ICT in teaching and learning PE, most PE teachers agreed that ICT usage is suitable and effective in teaching and learning PE. To conclude, most of the teachers' perception towards ICT usage are at the moderate level. However there is a significant relationship between perception towards effectiveness of ICT usage and levels of place of work. Regarding relationship between perception of ICT usage and ICT skils, there is a significant relationship between perception towards suitability of ICT usage and ICT skills. Finding also revealed that there is a significant relationship between perception towards anxiety of using ICT and ICT skills. As a conclusion, factors such as levels of place of work and gender have very little effect on perception towards utilization of ICT in teaching and learning PE among the PE teachers. The findings of this research implicate that PE teachers should be equipped with a higher level of ICT skills, ICT experiences and courses as well as ICT facilities before the Ministry of Education implement ICT assisted teaching and learning PE in the schools.